Applying Extensive Reading Strategy in Teaching Vocabulary at MA PP Nurul Azhar Talawe Sidrap - Rosmawati, Rosmawati; Patahuddin, Patahuddin; Nasrullah, Nasrullah (La Parole : Journal of Language Teaching and Pedagogy, 2023)
The students’ vocabulary at MA PP Nurul Azhar Talawe Sidrap is still lacking and need to improve. Based on observation, the researcher found several problems in students’ vocabulary. First, students are less interested in learning English and students’ awareness to memorize vocabulary is still lacking because students think there are many words that are difficult to understand. Second, students’ perception about learning English is difficult because there are many words they have to memorize. Therefore, the researcher proposed a solution to overcome this problem by implementing a different learning strategy, namely the extensive reading strategy. The purpose of this research is to find out whether the applying extensive reading strategy can increase students’ vocabulary. The researcher used a pre-experimental design with one group pre-test and post-test. The population of this research was the students of class XI MA PP Azhar Talawe Sidrap. The sample used purposive sampling. The sample of this research was class XI.A consists of 20 students. In collecting data, the researcher used vocabulary test which was divided into pre-test and post-test. The technique of analysis data used mean score and t-test formula for an independent sample. The result showed that the mean score of students in post-test (82) was higher than the mean score in pre-test (56,5). The standard deviation of the posttest was (7,6). At a significance level of 0,05 and degree of freedom (df) 19, the value of t-test (17,70) was higher than the t-table (1,729). As a result, the hypothesis H0 was rejected and H1 was accepted. The researcher concluded that the applying extensive reading strategy had improved the students’ vocabulary at MA PP Nurul Azhar Talawe Sidrap.